2007
DOI: 10.1089/ten.2006.0067
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Implantable Cartilaginous Structures from Bone Marrow–Derived Mesenchymal Stem Cells

Abstract: Fabrication of implantable cartilaginous structures that could be secured in the joint defect could provide an alternative therapeutic approach to prosthetic joint replacement. Herein we explored the possibility of using biodegradable hydrogels in combination with a polyglycolic acid (PGA) scaffold to provide an environment propitious to mesenchymal stem cells (MSCs) chondrogenic differentiation. We examined the influence of type I collagen gel and alginate combined with PGA meshes on the extracellular matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 55 publications
(53 reference statements)
1
23
0
Order By: Relevance
“…of studiesReferencesCell SourceNo. of studies a ReferencesHuman73[48, 50, 52, 53, 168236]Bone marrow62[48, 5053, 164, 168, 170173, 177180, 182185, 187, 188, 192, 195–197, 203, 206–210, 212, 216, 217, 219, 221, 223, 227, 230, 232235, 237–255]Rabbit17[240242, 246, 249, 252, 255–265]Adipose36[66, 169, 175, 176, 181, 186, 189, 193, 194, 199, 201, 202, 211, 214, 216, 218220, 224, 228, 229, 231, 235, 242, 256, 257, 260269]Bovine5[51, 164, 243, 245, 270]Synovium9[174, 191, 200…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…of studiesReferencesCell SourceNo. of studies a ReferencesHuman73[48, 50, 52, 53, 168236]Bone marrow62[48, 5053, 164, 168, 170173, 177180, 182185, 187, 188, 192, 195–197, 203, 206–210, 212, 216, 217, 219, 221, 223, 227, 230, 232235, 237–255]Rabbit17[240242, 246, 249, 252, 255–265]Adipose36[66, 169, 175, 176, 181, 186, 189, 193, 194, 199, 201, 202, 211, 214, 216, 218220, 224, 228, 229, 231, 235, 242, 256, 257, 260269]Bovine5[51, 164, 243, 245, 270]Synovium9[174, 191, 200…”
Section: Resultsmentioning
confidence: 99%
“…of studies (%)ReferencesGrowth factorNo. of studies (%)ReferencesTGF-β148 (44%)[50, 169175, 189, 190, 192, 193, 195, 199, 202, 208, 210, 211, 213, 214, 216, 217, 220, 222224, 228, 230–232, 234, 235, 244, 246, 249, 252256, 258, 260263, 266, 267, 270]SOX-51 (1%)[204]TGF-β332 (29%)[51, 162, 164, 168, 177, 181184, 197, 200, 205207, 218, 223225, 227, 237, 239, 240, 245, 247, 248, 250, 251, 257, 259, 267, 268, 270]SOX-61 (1%)[204]BMP-213 (12%)[188, 202, 213, 219, 225227, 229, 264, 265, 267, 270, 271]WNT3A1 (1%)…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogel–fiber composites are devised with the premise that the incorporation of a ductile fibrous network within a brittle hydrogel matrix increases the stiffness and fracture toughness of the hydrogel, enhancing energy absorption and preventing crack propagation [46, 47]. Fiber-reinforced hydrogels have been investigated in tissue engineering by incorporating a variety of polymeric fibers within hydrogel matrices [48, 49]. Structurally, fiber-reinforced hydrogel provides a discontinuous fibrous structure and proteoglycan matrix in native cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…In order to test this hypothesis, studies should be done to separately determine GAG synthesis and GAG deposition using radiolabelling techniques. It has recently been shown that alginate hydrogels within PGA scaffolds can aid GAG and collagen type II formation, probably due to retention of ECM molecules and chondrogenic growth factors within the construct (Hannouche et al 2007) or the maintenance of the appropriate cell shape, found in native cartilage.…”
Section: Discussionmentioning
confidence: 99%